2015
DOI: 10.1002/acp.3151
|View full text |Cite
|
Sign up to set email alerts
|

The Compensatory Role of Implementation Intentions for Young Adults with Low Working Memory Capacity

Abstract: We would like to thank Molly Magary and Michael Brodsky for their help in collecting the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The salient targets used in the PMD task may have been discrepant from other ongoing task stimuli, resulting in relatively automatic noticing of the target. However, participants then had to engage in controlled retrieval to recall the appropriate steps associated with the action plan, which reduces PM performance (Meeks et al, 2015). Like the results of the PMD task, we found that individuals with higher working memory had better PMR performance.…”
Section: Discussionsupporting
confidence: 52%
“…The salient targets used in the PMD task may have been discrepant from other ongoing task stimuli, resulting in relatively automatic noticing of the target. However, participants then had to engage in controlled retrieval to recall the appropriate steps associated with the action plan, which reduces PM performance (Meeks et al, 2015). Like the results of the PMD task, we found that individuals with higher working memory had better PMR performance.…”
Section: Discussionsupporting
confidence: 52%
“…Future researchers can examine how auditors' individual differences potentially interact with perceived fraud task importance and implementation intentions to affect auditor fraud performance. For example, psychology research finds that Type A personalities are more likely to carry out PM tasks successfully (Searleman 1996) and that implementation intentions interventions are particularly helpful at improving PM performance for individuals with lower rather than higher working memory capacity (Meeks et al 2015). Thus, future research should investigate individual differences that moderate the effects on auditor fraud performance noted in my study, as auditors with Type A personalities and/or high working memory capacity may exhibit the same (relatively higher) attention to fraud cues and fraud actions, regardless of elevated fraud task importance or implementation intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IIs are considered to be particularly helpful for individuals whose self-regulatory skills are compromised [ 21 ], thereby serving as a compensatory strategy for those in strongest need of assistance. This has been supported by a number of studies showing that IIs can help to overcome ego-depletion [ 41 ], and promote goal attainment among those suffering brain damage or drug addiction [ 42 , 43 ], as well as improve prospective memory performance among those with low executive functioning [ 44 , 45 ] or fluid mechanics (i.e., those cognitive functions that tend to decline with age; [ 46 ]). Accordingly, IIs have been suggested as a means to compensate for age-related decline in prospective memory [ 47 ].…”
Section: Introductionmentioning
confidence: 95%